The determinants of motorized mobility scooter driving ability after a stroke. Issue 25 (4th December 2021) - Ku, Fang-Ling; Chen, Wei-Chung; Chen, Ming-De; Tung, Szu-Ya; Chen, Tien-Wen; Tsai, Chiu-Chin
Abstract: Purpose: To investigate the determinants related to the ability to drive a motorized mobility scooter after a stroke. Method: The study was a cross-sectional study. The ability to drive a motorized mobility scooter was measured with the Power Mobility Clinical Driving Assessment. The independent variables included cognitive functions measured by the Color Trails Test and reaction time test, visual functions measured by a visual acuity test and visual field test, and motor functions measured with a dynamometer, the Box and Block Test, and the Functional Independence Measure. Results: The correlation analyses revealed that the Power Mobility Clinical Driving Assessment scores had significant correlations with reaction time ( ρ = −.65, p  < 0.01), binocular visual field ( r = .64, p < 0.01), binocular visual acuity ( r = .40, p  = 0.03), and the grip strength of the unaffected hand ( r = .47, p  = 0.01). The multiple regression analysis indicated that reaction time, binocular visual field, and the grip strength of the unaffected hand were the most significant determinants of the ability to drive a motorized mobility scooter ( R 2 = .76). Conclusions: The reaction time, binocular visual field, and grip strength of the unaffected hand were the most significant determinants related to the ability to drive a motorized mobility scooter after a stroke. IMPLICATIONS FOR REHABILITATION: Motorized mobility scooter driving ability for stroke patients is correlated with demographics (age, mobility scooter driving experience, time since last drive) and cognitive, visual and motor functions (reaction time, binocular visual field, visual acuity, and the grip strength of unaffected hand). Primary determinants of motorized mobility scooter driving ability for stroke patients include reaction time, binocular visual field, and grip strength of the unaffected hand. Comprehensive assessments incorporating cognitive, visual and motor functions are needed to evaluate the ability to drive a motorized mobility scooter after a stroke.